Implementation of Environmentally Friendly Packaging Design For Micro, Small and Medium Enterprise Products in Tangerang City - ary yanto (LPPM Universitas Yatsi Madani, 2025)
In this research, the researcher tries to discuss the application of environmentally friendly packaging design for Micro, Small and Medium Enterprises products in the Tangerang City environment, with increasing public awareness or what could be said as consumers regarding the issue of maintaining health, cleanliness and awareness of the environment, for Micro, Small and Medium Enterprises. It is hoped that it will be able to adapt to sustainable trends. The aim of this research is to explore the potential for packaging designs that are not only attractive but also contribute to reducing the environmental impact on society. The method used includes a survey of Micro, Small and Medium Enterprises and analysis of packaging designs that have been implemented. The research results show that the majority of Micro, Small and Medium Enterprises in Tangerang still use conventional packaging, although there is high interest in switching to environmentally friendly packaging, some Factors influencing this adoption include cost, knowledge of environmentally friendly materials, and full support from the Tangerang City Government in terms of policy. Recommendations from this research include education about the benefits of environmentally friendly packaging as well as developing partnerships between Micro, Small and Medium Enterprises and providers of sustainable packaging materials. It is hoped that by implementing better packaging design, Micro, Small and Medium Enterprises in Tangerang City can increase their competitiveness and contribute to environmental preservation, especially in the community and surrounding areas.